Relación entre estado nutricional y síntomas depresivos en personas de 50 años o más. Sabaneta (Antioquia-Colombia) 2015 (2016)
ABSTRACT: To determine nutritional status and symptoms of depression in adults, factors which are important to consider in the design of strategies that contribute to increasing quality of life. Objetive: To describe the relation between sociodomographic, nutritional, and depression factors in adults 50 years of age and older. Materials and methods: Descriptive cross-sectional study, in which sociodemographic, anthropometric, nutritional and mental health variables were determined in 168 adults aged 50 years and over, who belong to the Older Adult Program (PAM) of the city of Sabaneta, Antioquia. Results: We found significant differences between the variables body mass index (BMI), sex, and marital status, as well as in the nutritional minivaloration score (MNA) in relation to marital status (p <0.05). With the Beck depression score no significant relationships were found with sociodeomograhpic variables (P> 0.05), but significance was found with with MNA score (p <0.001). Conclusions: The findings make it possible to establish according to BMI and MNA, that participants generally have a favorable socioeconomic situation and an adequate nutritional status; In addition, the frequency was low of depression symptoms, contributing to the health status and well-being of adults belonging to the PAM.